2020
DOI: 10.1186/s12862-020-01606-7
|View full text |Cite
|
Sign up to set email alerts
|

Shifting evolutionary sands: transcriptome characterization of the Aptostichus atomarius species complex

Abstract: Background: Mygalomorph spiders represent a diverse, yet understudied lineage for which genomic level data has only recently become accessible through high-throughput genomic and transcriptomic sequencing methods. The Aptostichus atomarius species complex (family Euctenizidae) includes two coastal dune endemic members, each with inland sister speciesaffording exploration of dune adaptation associated patterns at the transcriptomic level. We apply an RNAseq approach to examine gene family conservation across th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…atomarius species complex based on mitochondrial data plus evidence of adaptive divergence (i.e., coastal dune habitats and lighter abdominal coloration). In a follow‐up study, Garrison et al ( 2020 ) found evidence of chemosensory‐associated gene families under selection in dune endemics compared with their inland sister lineages, further elucidating patterns of ecological differentiation between coastal and inland sister species. Another example within mygalomorphs includes Newton et al ( 2020 ) who initially identified five genetically distinct lineages within the Antrodiaetus unicolor species complex; however, genetic and ecological exchangeability assessments led to the delimitation of three species, not five, based on molecular, behavioral, and morphological data.…”
Section: Discussionmentioning
confidence: 99%
“…atomarius species complex based on mitochondrial data plus evidence of adaptive divergence (i.e., coastal dune habitats and lighter abdominal coloration). In a follow‐up study, Garrison et al ( 2020 ) found evidence of chemosensory‐associated gene families under selection in dune endemics compared with their inland sister lineages, further elucidating patterns of ecological differentiation between coastal and inland sister species. Another example within mygalomorphs includes Newton et al ( 2020 ) who initially identified five genetically distinct lineages within the Antrodiaetus unicolor species complex; however, genetic and ecological exchangeability assessments led to the delimitation of three species, not five, based on molecular, behavioral, and morphological data.…”
Section: Discussionmentioning
confidence: 99%
“…Establishing the structure and divergence levels within P . clathrata will facilitate a comparative approach to testing possible ecological and behavioral reproductive barriers (Bond & Stockman, 2008; Chambers et al., 2023; Garrison et al., 2020; Masta & Maddison, 2002; Newton et al., 2020; Starrett et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…No obvious differences in genitalic and somatic morphology occur for males from the two main populations of P. clathrata, but limited sample size prevents more formal analyses . Establishing the structure and divergence levels within P. clathrata will facilitate a comparative approach to testing possible ecological and behavioral reproductive barriers Chambers et al, 2023;Garrison et al, 2020;Masta & Maddison, 2002;Newton et al, 2020;Starrett et al, 2018).…”
Section: Speciation Dynamicsmentioning
confidence: 99%